2000
DOI: 10.1556/aalim.29.2000.4.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fat Rich Diet and Alcohol on Ion Concentration in Bile Fluid in Rats

Abstract: The metabolic alteration of fatty liver causes significant changes in the composition of bile fluid secreted by epithelial liver cells. These processes include both organic molecular and inorganic ion content changes in bile juice as well. In this work ion concentration differences of bile fluid in experimental hyperlipidemic rats compared to normal ones were monitored. Fatty liver in young male Wistar albino rats was induced by 2% cholesterol, 20% sunflower oil and 0.5% cholic acid added to the normal food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…After digestion of the samples in nitric acid (5 ml, 65%) and H 2 O 2 (2 ml, 30%), an inductively coupled plasma (IPC) optical emission spectrometric method was used for measuring the metal content in a Spectro Genesis ICP equipment (Spectro Analytical Instruments GmbH, Kleve, Germany). 41 For the standardization of equipment and measurements of elements, Spectro multielement and Spectrum 3D standards were used. A computer-guided TraceLab 50 type polarographic–voltammetric analyzer was used for the voltammetric determination of Se at −550 mV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After digestion of the samples in nitric acid (5 ml, 65%) and H 2 O 2 (2 ml, 30%), an inductively coupled plasma (IPC) optical emission spectrometric method was used for measuring the metal content in a Spectro Genesis ICP equipment (Spectro Analytical Instruments GmbH, Kleve, Germany). 41 For the standardization of equipment and measurements of elements, Spectro multielement and Spectrum 3D standards were used. A computer-guided TraceLab 50 type polarographic–voltammetric analyzer was used for the voltammetric determination of Se at −550 mV.…”
Section: Methodsmentioning
confidence: 99%
“…After digestion of the samples in nitric acid (5 ml 65%) and hydrogen peroxide (2 ml 30%), an inductively coupled plasma optical emission spectrometric (ICP-OES) method was used for measuring metal content 43 in a Spectro Genesis ICP equipment (Kleve, Germany). For the standardization of equipment and measurements of elements Spectro multielement and Spectrum 3D standards were used.…”
Section: Metal Contents In the Plasma And Kidneymentioning
confidence: 99%
“…As mentioned in the introduction, the way in which the MgSO 4 molecule exerts an antioxidative effect in many diseases related to LPO is unclear at present. Several experimental works have reported that magnesium compounds are effective hydroxyl radical scavengers . In this sense, calculations with different approaches for electronic structure methods were performed with small systems to validate the results by comparison between them and with other theoretical calculations from the literature.…”
Section: Resultsmentioning
confidence: 98%
“…However, due to their high mobility and reactivity, • OH radicals may be trapped by the MgSO 4 CIP, as shown below, to prevent the reaction with H atoms of unsaturated fatty acid residues. This is feasible because, as aforementioned, experimental researchers have found that the MgSO 4 salt is a hydroxyl radical scavenger …”
Section: Resultsmentioning
confidence: 99%
“…After digestion of the liver samples (protein content: 10 mg/ml) with a mixture of nitric acid and hydrogen peroxide and dilution with deionised water, the concentration of seven elements (Ca, Cu, Fe, Mg, Mn, P, Zn) was determined. Three times 3 s integration time, blank subtraction and background correction were applied during the measurements [26].…”
Section: Surgical Modelmentioning
confidence: 99%